2021
DOI: 10.1038/s41598-021-03572-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of deep learning algorithms for diagnosing bacterial keratitis via external eye photographs

Abstract: Bacterial keratitis (BK), a painful and fulminant bacterial infection of the cornea, is the most common type of vision-threatening infectious keratitis (IK). A rapid clinical diagnosis by an ophthalmologist may often help prevent BK patients from progression to corneal melting or even perforation, but many rural areas cannot afford an ophthalmologist. Thanks to the rapid development of deep learning (DL) algorithms, artificial intelligence via image could provide an immediate screening and recommendation for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 25 publications
0
36
0
1
Order By: Relevance
“…Algorithms such as ResNet, DenseNet, ResNeXt, SENet, VGG and EfcientNet can potentially develop models for image diagnosis of BK. 54,57 A study from Thailand used three algorithms, DenseNet121, REstNet50, VGG19 to classify images of patients with infectious keratitis. The test accuracy (F1 score) was higher for VGG19 (78%) followed by DenseNet121 (71%) and REstNet50 (68%).…”
Section: Deep Learningmentioning
confidence: 99%
See 4 more Smart Citations
“…Algorithms such as ResNet, DenseNet, ResNeXt, SENet, VGG and EfcientNet can potentially develop models for image diagnosis of BK. 54,57 A study from Thailand used three algorithms, DenseNet121, REstNet50, VGG19 to classify images of patients with infectious keratitis. The test accuracy (F1 score) was higher for VGG19 (78%) followed by DenseNet121 (71%) and REstNet50 (68%).…”
Section: Deep Learningmentioning
confidence: 99%
“…57 Investigators using external eye photographs to assess deep learning frameworks in BK have reported that the diagnostic accuracy of different models ranged from 69% to 72%; comparable to ophthalmologists (66% to 74%). 54 In areas or circumstances where patients are unable to access ophthalmic care, the ability to diagnose and assess microbial keratitis through artificial intelligence using external eye photos, such as could be taken with a mobile phone, may allow for appropriate therapy to be commenced without delay. 2,5,[54][55][56] 3 | HERPES SIMPLEX KERATITIS…”
Section: Deep Learningmentioning
confidence: 99%
See 3 more Smart Citations